2021
DOI: 10.1002/jmr.2924
|View full text |Cite
|
Sign up to set email alerts
|

The moonlighting activities of dihydrolipoamide dehydrogenase: Biotechnological and biomedical applications

Abstract: Dihydrolipoamide dehydrogenase (DLDH) is a homodimeric flavin-dependent enzyme that catalyzes the NAD + -dependent oxidation of dihydrolipoamide. The enzyme is part of several multi-enzyme complexes such as the Pyruvate Dehydrogenase system that transforms pyruvate into acetyl-co-A. Concomitantly with its redox activity, DLDH produces Reactive Oxygen Species (ROS), which are involved in cellular apoptotic processes. DLDH possesses several moonlighting functions. One of these is the capacity to adhere to metal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 167 publications
0
5
0
Order By: Relevance
“…The DLD gene encodes a member of the class I pyridine nucleotide-disul de oxidoreductase family that plays multiple roles in the decarboxylation of pyruvate and the oxidation of dihydrolipoamide and is involved in constituting α-keto acid dehydrogenase complexes (e.g. α-ketoglutarate dehydrogenase, αketoadipate dehydrogenase and glycine decarboxylase) 6, [23][24][25] .DLD is a mitochondrial respiration-dependent copper ion carrier induced novel regulated positive regulators of cell death that regulate copper-dependent cell death by affecting the tumor TCA cycle and the underlying biosynthetic processes that support tumor growth, which may provide new ideas for the therapeutic action of certain cancer-targeted drugs 5,26 . Previous studies have found that DLD is involved in constituting pyruvate dehydrogenase complex and α-ketoglutarate dehydrogenase complex, which are associated with several fatal metabolic diseases and have been identi ed as important metabolic targets in cancer [27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…The DLD gene encodes a member of the class I pyridine nucleotide-disul de oxidoreductase family that plays multiple roles in the decarboxylation of pyruvate and the oxidation of dihydrolipoamide and is involved in constituting α-keto acid dehydrogenase complexes (e.g. α-ketoglutarate dehydrogenase, αketoadipate dehydrogenase and glycine decarboxylase) 6, [23][24][25] .DLD is a mitochondrial respiration-dependent copper ion carrier induced novel regulated positive regulators of cell death that regulate copper-dependent cell death by affecting the tumor TCA cycle and the underlying biosynthetic processes that support tumor growth, which may provide new ideas for the therapeutic action of certain cancer-targeted drugs 5,26 . Previous studies have found that DLD is involved in constituting pyruvate dehydrogenase complex and α-ketoglutarate dehydrogenase complex, which are associated with several fatal metabolic diseases and have been identi ed as important metabolic targets in cancer [27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…FDX1 may modulate TP73 tumor suppressor through IRP2 to regulate tumor suppression ( Zhang et al, 2020a ), and FDX1 may be a gene related to KIRC ( Khouja et al, 2022 ). DLD is a homodimeric flavin-dependent enzyme that catalyzes NAD + -dependent oxidation of dihydrolipoamide and participates in the TCA cycle to convert pyruvate to acetyl-CoA ( Fleminger and Dayan, 2021 ). DLD may destroy cancer cells by producing ROS and by chelation with DNA ( Dayan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dihydrolipoamide dehydrogenase encoded by the DLD gene is a homologous flavin-dependent enzyme that catalyses NAD + -dependent dihydrolipoamide oxidation. It is involved in regulating apoptosis by producing ROS, and its enzyme activity is associated with tumor and apoptotic cell death [ 27 ]. We hypothesised that higher expression of the DLD gene in the high-risk group might indicate more ROS production.…”
Section: Discussionmentioning
confidence: 99%